Chat Language and the Challenges of Students in Written Composition - Chijioke, Dorathy Ijeoma; Nwala, Michael Alozie (Celt: A Journal of Culture, English Language Teaching & Literature, 2019)
With the prevalence of the internet and social network platforms in this digital age, most people opt for text messages as a fast and convenient means of communication and prefer real-time online chats to face-to-face social interactions. The cyber language is replete with writing errors that are not conventionally acceptable in academic writing and which can impede comprehension in some cases. As teenage participation in this new media increases, this study investigated the impact of chat language on the written composition of senior secondary school students who are prospective candidates for O’level and or A’level examinations. Data were generated from the students’ written essay scripts and analysed using Halliday’s Systemic Functional Grammar as the theoretical framework. The study adopted the quantitative and qualitative research methods in which 842 senior secondary 2 and 3 (SS2 and SS3) students of selected schools in Port Harcourt, Rivers State, are the population. The result revealed that online chat language and text-based messages mostly affect students’ writings in mechanical accuracy and expression. The study therefore recommended that the negative effects of the social media on the students’ writings should be checked in schools.